The Transparency and Accountability Learning of the Spanish Municipalities - Fernández-Gómez, Erika; Segado-Boj, Francisco; Díaz-Campo, Jesús; Manfredi-Sánchez, Juan Luis (Revista del CLAD Reforma y Democracia, 2019)
This article studies the instrumental development of transparency in the Spanish municipalities’ websites between 2011-2017, under two different regulations on transparency and good governance. The research method consists of the study of 41 indicators, later expanded to 52 to adjust it to the reform of the legislation on transparency and access to public information, approved in 2013. The general objective is the investigation of the resources, the traits and the practices of public communication that the municipalities carry out through the web. The particular goal is the identification of these resources on the websites, as well as the possible structural and message deficiencies. The indicators are published and updated in successive waves into the Map Infoparticip@ platform (http://www.mapainfoparticipa.com). The research work has a universe of 2,930 municipalities, although the sample used for this article is reduced to 400 cities that have more than 20,001 registered inhabitants. This sample allows a qualitative analysis that include what variations have been observed, what type of treatment is offered or what citizen services have appeared in the period. The result of this paper announces that the regulation on transparency, access to public information and good governance does not ensure better results in the publication of information on municipal websites. The indicators analyzed offer worse results, regardless the size of the municipality or the change in ownership and political orientation of the mayor's officeIt advocates, on the other hand, for a culture of broader transparency that involves civil society and encourages citizen participation. The legal approach to transparency issues reduces its positive effect on the public management of municipalities.
Keywords: Transparency; Accountability; Administrative Accountability; Administrative Corruption; Public Communication; Access to Information; Government Information; Internet; Municipalities; Spain